Preparation, structural characterization, bioactivities, and potential clinical applications of the polysaccharides from Paris polyphylla: a review - Sha, Ailong; Li, Yuanyuan (Frontiers in Pharmacology, 2025)
The [Paris polyphylla Smith var. Yunnanensis (Franch.) Hand. - Mazz] (The following is denoted by P. polyphylla) contains various chemical components such as steroidal saponins, flavonoids, polysaccharides, amino acids, etc. It is a traditional Chinese medicinal herb with important medicinal value. So far, the pharmacological research on P. polyphylla at home and abroad mainly focuses on compounds such as saponins and flavonoids, and there are relatively few reports on the study of P. polyphylla polysaccharides. In recent years, with the continuous deepening of research on the P. polyphylla, scientific and technological workers have gradually realized the application value of the polysaccharides from P. polyphylla, and the research of it has been increasing year by year. This article provides a review of the preparation, structural characterization, bioactivities, and potential clinical applications of the polysaccharides from P. polyphylla, aiming to provide a reference for the development, application, and further research.